Special economic zones: key lessons learned from the global experience - Pidorycheva, I. (Економічний вісник Донбасу, 2017)
Special economic zones are one of the oldest economic regulators which are widespread throughout the world. The study showed that zones can be an effective instrument to attract foreign investment, create new jobs, stimulate manufactured production, increase export revenues, promote structural transformation, and ultimately ensure country’s economic development, but only when they are created in accordance with all the necessary conditions. This paper focuses on the study of various issues and opportunities that accompany the process of SEZs’ creation by analyzing the conditions that lead to success or failure of implementation this instrument in practice. Attention was paid to Ukrainian experience of SEZs’ establishing and to a question on why in Ukraine attempt to use this instrument of economic policy had proved unsuccessful and what needs to be done primarily to remedy this situation. Спеціальні економічні зони є одним із найстаріших економічних регуляторів, які поширені в усьому світі. Дослідження показало, що зони можуть бути ефективним інструментом залучення іноземних інвестицій, створення нових робочих місць, стимулювання промислового виробництва, збільшення доходів від експорту, сприяння структурним перетворенням і, в кінцевому підсумку, – забезпечити економічний розвиток країни, але тільки коли створюються з дотриманням певних умов. У даній статті основна увага приділяється дослідженню проблем і можливостей, які супроводжують процес створення спеціальних економічних зон, шляхом аналізу умов, які приводять до успіху або невдачі в реалізації цього інструменту на практиці. Приділяється увага українському досвіду створення спеціальних економічних зон і питанню того, чому в Україні спроба використати цей інструмент економічної політики зазнала невдачі і що необхідно зробити в першу чергу для виправлення цієї ситуації. Специальные экономические зоны являются одним из старейших экономических регуляторов, распространенных во всем мире. Исследование показало, что зоны могут быть эффективным инструментом привлечения иностранных инвестиций, создания новых рабочих мест, стимулирования промышленного производства, увеличения доходов от экспорта, содействия структурным трансформациям и, в конечном счете, – обеспечить экономическое развитие страны, но только когда создаются с соблюдением определенных условий. В данной статье основное внимание уделяется исследованию проблем и возможностей, которые сопровождают процесс создания специальных экономических зон, путем анализа условий, которые приводят к успеху или неудаче в реализации этого инструмента на практике. Уделяется внимание украинскому опыту создания специальных экономических зон и вопросу того, почему в Украине попытка использовать этот инструмент экономической политики потерпела неудачу и что необходимо сделать в первую очередь для исправления этой ситуации.